Curved oligonucleotide constructs as human topoisomerase I inhibitors : a mechanistic study of the enzyme’s recognizing passway. - Zhao, Guanjia. (2010)
Topoisomerases I are enzymes that alter the topological states of DNA. In eukaryotic organisms, including human being, Topoisomerase I is diverse and significant. It is discovered that there are more than normal amount of Topo I enzymes in the tumour cells, making it a potential drug target for cancer therapy. The traditional Topo I inhibitors are organic molecules, and this report aims to develope short oligonucleotides as possible Topo I inhibitors, and also to study the recognition mechanism of human Topoisomerase I with the substrate DNA molecules. In this project, it was not only evidenced that DNA curvature indeed was crucial for the enzyme-substrate recognition, but also the minimum number of A-tracts in the curved constructs was determined. What’s more, inhibitory effects of different types of curvature on Topo I were compared to show that a two-way-curved oligonucleotide was more effective to inhibit Topo I activity than the corresponding one-way-curved oligonucleotide, and this finding might be helpful for better understanding of the enzyme-DNA recognition mechanism.